2016
DOI: 10.1002/jcb.25614
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐Pyrano Prenyl Isoflavone Improves Glucose Homeostasis by Inhibiting Dipeptidyl Peptidase‐4 in Hyperglycemic Rats

Abstract: Isoflavones widely distributed in plants prevent diabetes. This study investigated the in vivo and in vitro effect of 3',4'-dihydroxy-6″,6″,6″',6″'-tetramethylbis(pyrano[2″,3″:5,6::2″',3″':7,8]isoflavone (bis-pyrano prenyl isoflavone) on glucose homeostasis in hyperglycemic rats. The ethyl acetate fraction from aerial parts of Polygala molluginifolia that contain isoflavones was assayed on glucose tolerance, on in vitro maltase activity and on protein glycation. The isoflavone bis-pyrano prenyl isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
9
0
2
Order By: Relevance
“…Altenhofen et al [38] showed that the acute in vivo effect of the major compound isolated from the aerial parts of Polygala molluginifolia, bis-pyrano prenyl isoflavone, exhibits an antihyperglycemic effect by improving glucose tolerance, stimulating GLP-1 secretion (increased serum GLP-1 levels) and inhibiting DPP-4 activity (decreased serum DPP-4 activity) beyond the increase of insulin secretion in hyperglycemic rats. Furuhashi et al [39] reported on a study where sitagliptin (50 mg/day), a dipeptidyl peptidase 4 (DPP-4) inhibitor that increases GLP-1, was administered to patients with type 2 diabetes (n = 24) for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Altenhofen et al [38] showed that the acute in vivo effect of the major compound isolated from the aerial parts of Polygala molluginifolia, bis-pyrano prenyl isoflavone, exhibits an antihyperglycemic effect by improving glucose tolerance, stimulating GLP-1 secretion (increased serum GLP-1 levels) and inhibiting DPP-4 activity (decreased serum DPP-4 activity) beyond the increase of insulin secretion in hyperglycemic rats. Furuhashi et al [39] reported on a study where sitagliptin (50 mg/day), a dipeptidyl peptidase 4 (DPP-4) inhibitor that increases GLP-1, was administered to patients with type 2 diabetes (n = 24) for 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this herbal drug provides a hypoglycemic response through DPP-IV inhibition pathway. Flavonoids play a role in DPP-IV inhibition [ 8 , 4 , 30 ] and have also been studied as GLP-1 receptor agonists [ 31 ]. In our previous study, we have proved PTWE as a competitive inhibitor of DPP-IV [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been studied that DPP-IV inhibitor bis-pyranoprenyl isolated from ethyl acetate fraction from aerial parts of Polygala molluginifolia contributes to GLP-1 secretion through the stimulation of calcium influx in the intestine. The overall mechanism involves voltage-dependent calcium channels, phospholipase C, protein kinase C, and stored calcium [ 30 ]. As the compositions of all DPP-IV inhibitory plants found in nature are different, the above-discussed pathway must be the common mechanism, with minor modifications for each plant, through which GLP-1 secretion could be enhanced through DPP-IV inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 was estimated by means of colorimetric measurements at 450 and 590 nm with an ELISA plate reader (Organon Teknika, Roseland, NJ) by interpolation from a standard curve. Samples were analyzed in duplicate in each group and results were expressed as serum GLP-1 (pM; Altenhofen et al, 2017).…”
Section: Oral Glucose Tolerance Test In the Presence Of Sitagliptin For Glp-1 Measurementsmentioning
confidence: 99%